(untitled) (Global Journal of Medical Research, 2016)
As nature has selected amphibian skin defensive peptides for inter-species delivery through the oral route in the recipient, structural stabilisation modifications may have occurred to facilitate this and such information would be most useful and could potentially provide new insights to the design of orally-active and selectively-targeted peptide therapeutics. The purposes of this study were to study catabolic pathways in saliva for selected but commonly occurring bioactive peptide types belonging to the protease inhibitor (PI) and bradykinin-related peptide (BRP) families, namely pLR (LVRGCWTKS-YPPKPCFVR), HV-BBI (SVIGCWTKSIPPRPC FVK) and I-11-R (IRRPPGFSPLR), and to extend this study by determining catabolic pathways with kallikrein -the major salivary protease. These data will aid in the establishment of a database of peptide stabilities that may be useful in the design of future orally-delivered peptide therapeutics.